Tarqiyatu fahmi al-Mufradāti bi-sti’māli al-Aflāmi al-‘arabiyyati Li talāmīżi al-Ṣaffi al-Ṡāni bi al-Madrasati al-‘āliyati al-Hukūmiyyati al-Ṡāniyati bi Bandung - Jaka Imam; Wildana Wargadinata (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2020)
The lack of mastery of mufradāt is one of the factors of the difficulty in mastering language skills, and Madrasah in particular does not have material specifically devoted to mufradāt. Mufradāt is taught along with language skills. This is intended to help students focus on the mahārah which must be mastered. This article aims to increase the understanding and mastery of mufradāt in Madrasah Aliyah in grade 11 of MAN 2 Padang Religious Program. The problem that arises in this school is the lack of mastery of mufradāt in students which makes it difficult for them to understand teaching materials. Based on that, this research is limited to three important points; the technique of using film media in learning mufradāt,, the levels of students' mastery of mufradāt before the action, and the level of mastery of students in mufradāt after the action. The study used classroom action research method which is carried out in two cycles. The results of the study show that the steps in using film media have several points, giving a list of mufradāt, watching the film, reading the text hiwār from the film, giving difficult vocabulary and test. In the first cycle the value of students previously 66% to decreased to 58.37%, while in the second cycle increased to 86.46%. Keywords: Film, Arabic Learning, Arabic Vocabulary